The Caliphate and Islamic statehood formation, fragmentation and modern interpretation - Kersten, Carool (Critical surveys in Islamic studies, 2015)
"This three-volume reference work tracks the history of the Caliphate as what many Muslims believe to be a genuine and authentic Islamic political institution: From its emergence in seventh-century Arabia until highly contested and controversial attempts of its revival at the beginning of the twenty-first century by radical Islamists in Afghanistan and Iraq. No matter how randiose such interpretations of a seemingly archaic institution may be, they show the Caliphate's longevity as a rallying point real or symbolic for Muslims across the world."--Page 4 of cover (each volume).